On the concept of university competitiveness management - E. V. Pirogova (Вестник университета)
Operating under market economy conditions, higher education institutions should develop a set of strategic measures to ensure their competitiveness. The system of views on solving the problems of achieving and keeping competitive advantage is mainly represented by the concept of managing the competitiveness of higher education institutions. The article is devoted to identifying the features and clarifying the content of this concept. It is determined that its content is a set of goals, principles, functions, methods, and tools that ensure the competitiveness of a university in the educational services market. The aforementioned content components are analysed in detail. Methods of managing university competitiveness are substantiated and classified based on the type of controlling influence. Tools for managing competitiveness are described, including in terms of their impact on end users of scientific and educational products (services).